Presenting the model of self-care behaviors of pregnant women based on health literacy and mindfulness with the mediation of a health-oriented lifestyle - Rezvani, Seyedeh Reyhaneh; Abolghasemi, Shahnam; Farhangi, Abdolhassan (Applied Family Therapy Journal (AFTJ), 2022)
Aim: This research was conducted with the aim of presenting the pattern of self-care behaviors of pregnant women based on health literacy and mindfulness with the mediation of a health-oriented lifestyle. Methods: The current research was applied in terms of its purpose and structural equations in terms of descriptive-correlation method. The studied population was pregnant women referring to comprehensive health centers in Bojnord city in the last three months of 2021. A number of 240 pregnant women who volunteered to participate in the research were selected through available sampling. Data using the pregnancy health literacy questionnaire of Kharazi, Piman and Esmaeili (2015), the mindfulness questionnaire of Chadwick, Hember, Sims, Peters, Kupers et al. 2013) and the health-oriented lifestyle questionnaire of Walker and Hale-Polersky (1997) were obtained, and the variables were defined and information was entered using SPSS24 and AMOS statistical software, and it was analyzed using the statistical methods of path analysis and structural modeling. Results: The results show that the structural relationship of pregnant women’s self-care behaviors based on health literacy and mindfulness is suitable with the mediation of health-oriented lifestyle. In the final research model, the relationship between variables of self-care behaviors of pregnant women based on health literacy (β=0.50, P<0.001) and mindfulness (β=0.47, P<0.001) with the mediation of health-oriented lifestyle It was positive and meaningful. Conclusion: It can be concluded that according to the estimated indicators, the structural relationship of self-care behaviors of pregnant women based on health literacy and mindfulness with the mediation of health-oriented lifestyle has a good fit.